Problemy w modelowaniu przy użyciu rozkładów α-stabilnych - Stachura, Michał (Problems with modelling with use of α-stable distributions, 2006)
The paper treats of some dangers and obstacles that may emerge when modeling data with use of a-stable distributions. These problems are illustrated by a simple simulation example and by an analysis of properly chosen empirical data alike. The carried research shows strong sensitivity of a-stable distribution parameter estimates. It is also shown that empirical data analysis may lead to unsolvable questions unfortunately. The goal of the paper is not to discourage for using a-stable distributions but to emphasize that a-stable modelling is under the necessity of special caution, careful data analysis and of giving non-statistic arguments that could additionally validate usage of a-stable distributions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 491-499